2016
DOI: 10.3201/eid2201.151384
|View full text |Cite
|
Sign up to set email alerts
|

Multiorgan WU Polyomavirus Infection in Bone Marrow Transplant Recipient

Abstract: Virus was detected in the lung and trachea of a deceased patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…PCR-based studies of 30 lung cancer patients compared to healthy individuals indicated no direct association between WUV infection and lung adenocarcinoma (38). However, recently, a lung transplant patient with Job’s syndrome and a bone marrow transplant recipient with severe acute respiratory distress syndrome were reported to have WUV pulmonary infection (29, 39). In the present study, we have identified a case of WUV-associated bronchitis with the demonstration of both early and late viral antigens in intact dysplastic lung epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…PCR-based studies of 30 lung cancer patients compared to healthy individuals indicated no direct association between WUV infection and lung adenocarcinoma (38). However, recently, a lung transplant patient with Job’s syndrome and a bone marrow transplant recipient with severe acute respiratory distress syndrome were reported to have WUV pulmonary infection (29, 39). In the present study, we have identified a case of WUV-associated bronchitis with the demonstration of both early and late viral antigens in intact dysplastic lung epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…Toptan et al [13] developed a panhuman PyV immunohistochemistry test and analysed 1,250 samples from various, also lung, tumours and normal tissues (detailed in Table 3), and antigen positivity was revealed in a lung tissue sample from a patient with chronic lymphocytic leukaemia, then the presence of WUPyV DNA was also proved. Siebrasse et al[14, 15] studied KIPyV and WUPyV in lung tissue samples from 2 patients not only by PCR, but also by antibodies, revealing antigen positivity. KIPyV-positive cells were identified as CD68+, suggesting that alveolar macrophages might be infected by the virus.…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemistry was performed on lung, trachea, liver, kidney, and gastrointestinal tract tissue sections from a bone marrow transplant patient by anti-VP1 WUPyV antibody. Viral antigen-positive cells were found in trachea and lung sections; some cells were CD68+ and showed macrophage morphology [15]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KIPyV and WUPyV have been detected worldwide in respiratory specimens and clinical samples (Babakir-Mina et al 2008Kiasari et al 2008;Bialasiewicz et al 2008;Foulongne et al 2008;Payungporn et al 2008;Abed et al 2007;Han et al 2007;Le et al 2007), suggesting a widespread infection, but their involvement in human disease or tumor development is not clear (Giraud et al 2008(Giraud et al , 2009). Reactivation and excretion of KIPyV and WUPyV have also been reported in the gastrointestinal tract of immunosuppressed transplanted patients (Siebrasse et al 2016) and in HIV patients.…”
Section: Kipyv and Wupyvmentioning
confidence: 99%